Students’ Perceptions of Readiness toward English for Islamic Teaching Course in Online Learning during Next Normal - Abdul Hamid; Basya, Dihliza; Mahbub, Moh. Arif (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2024)
In online learning, various problems that are often encountered are slow to understand the material, communication abilities, social abilities and weak internet networks. EfIT learning is carried out online which results in the emergence of many perceptions because online learning is very different from face-to-face learning. This study discusses students' perceptions of readiness for EfIT lessons in learning online during next normal. This qualitative interview study (Kvale, 2007) aimed at investigate Students’ Perceptions of Readiness Toward English for Islamic Teaching Course in Online Learning During next Normal. The data collected from-semi structure interview with four participants at one of the private university in the eastern of java, Indonesia. The result indicate that the readiness online learning in EfIT courses is quite good, especially in mastering technology.